The Correlation between Parenting Pattern and Stunting in Toddlers Aged 24-36 Months in Percut Sei Tuan District Deli Serdang Regency - Dika Saraswati; Etti Sudaryati; Jumirah Jumirah (RIRAI Publisher, 2023)
Stunting is a major cause of high mortality (mortality) and morbidity (morbidity) in toddlers under five years of age. The Integrated Toddler Nutrition Status Study (SSGBI) and Susenas (2020) explain that the prevalence of stunting in Deli Serdang Regency is 30.97%. The aim of this study is to find the correlation between parent patterns and stunting case at age of 24-36 months toddlers in Percut Sei Tuan District Deli Serdang Regency. This research is a quantitative study with a Cross Sectional Study design. Data analysis used the chi-square test with a sample of 100 mothers with toddlers aged 24-36 months. The results showed that the related variables were exclusive breastfeeding (p=0.026), breastfeeding experiences for > 2 years old toddlers (p=0.026) and basic immunization (p=0.017) with stunting.